The Influence of Influencer Marketing, Brand Image and Electronic Word of Mouth on Emina Skincare Purchase Decisions in Generation Z in Cirebon City - Mulyasari, Nina; Hernidatiatin, Lis Tatin (Jurnal Manajemen, 2026)
This study examines the influence of influencer marketing, brand image, and electronic word of mouth (e-WOM) on purchasing decisions for Emina skincare products among Generation Z consumers in Cirebon City. Using a quantitative associative approach, data were collected through questionnaires from 200 respondents and analyzed using multiple linear regression. The findings indicate that influencer marketing, brand image, and e-WOM each have a positive and significant effect on purchasing decisions, both partially and simultaneously (p < 0.05). Among these variables, brand image emerges as the most dominant factor, followed by e-WOM and influencer marketing. The coefficient of determination shows that the three variables explain a substantial proportion of variation in purchasing decisions (R² ≈ 0.85), indicating a strong explanatory power of the model. These results suggest that purchasing decisions among Generation Z are shaped not only by promotional exposure through influencers but also by brand credibility and peer-generated online information. This study contributes contextually by providing empirical evidence from a medium-sized city and focusing on a local skincare brand, offering insights into how digital marketing strategies operate among Generation Z consumers outside major metropolitan areas.